Effect of injection of love-dart mucus on physical vigour in land snails: can remating suppression be explained by physical damage?. Issue 3 (2nd July 2016) - Kimura, K.; Shibuya, K.; Chiba, S.
Abstract : We investigated a conspicuous mating behaviour of simultaneously hermaphroditic land snails, the so-called shooting of love-darts, whereby a snail pushes its love-dart(s) into its mating partner. It has been shown that a specific mucus coating the love-dart is transferred into the partner's blood and it suppresses subsequent matings in the darted individual in Euhadra quaesita . However, how the dart mucus suppresses subsequent matings is still unclear. In the present study, we tested a hypothesis for the underlying mechanisms: sperm donors reduce physical vigour in mating partners through injection of the dart mucus. In observational experiments, we found that neither locomotion behaviour nor food consumption differed between snails artificially injected with the mucus and snails injected with a control solution. These findings show that the dart mucus can suppress subsequent matings in the partners without affecting physical condition.